IMPLEMENTATION OF THE SIAK RIVER BASIN MANAGEMENT PROGRAMME IN THE CITY OF PEKANBARU - Febriyana, Anggita; Meilani, Nur Laila (TOPLAMA, 2025)
This study is motivated by the pollution of the Siak River in Pekanbaru City, caused by the large amount of waste in the Siak River Basin (DAS) and frequent flooding due to high rainfall and inadequate water retention capacity. Additionally, the low public awareness of maintaining river cleanliness poses a challenge for the government. To address this issue, the government launched the Siak River Basin management program. This study aims to describe and analyze the implementation of the program and identify the inhibiting factors. The method used is qualitative research with the MSN approach (Mentality, System, and Networking). Data were collected through observation, interviews, and documentation. The results indicate that the program’s implementation has not been optimal due to several obstacles, including limited budget, inadequate land availability, low public awareness, ineffective socialization, and poor coordination among institutions. This study provides recommendations to improve the effectiveness of the Siak River Basin management program.